What affects chronic lithium poisoning in psychiatric patients? - a case report - Pożarowska, Kinga; Rudziński, Gracjan; Brzuszkiewicz, Kinga; Tchórz, Michał (Journal of Education, Health and Sport, 2022)
INTRODUCTION: Despite medical developments, drug poisoning still occurs. Lithium is a drug that has been used for more than 60 years as a mood stabilizer in the treatment and prevention of bipolar disorder, mania and recurrent depression. Lithium is the most commonly prescribed mood stabilizer. It has a narrow therapeutic index. Its target concentration in acute mania should be 0.6-1.5 mEq/L and 0.6-0.8 mEq/L for maintenance therapy. Because of this, there is a risk of lithium intoxication. We would like to present to you the case of a patient with chronic lithium poisoning. MATERIALS AND METHOD: Patient information was collected from hospital records available in the clinical toxicology department. In addition, we conducted a literature review on lithium treatment, its toxicity, side effects and pharmacokinetics using PubMed. CASE REPORT: The patient, 58, was referred for lithium poisoning and admitted to the Clinical Toxicology and Cardiology Department in Lublin for treatment. The patient had a previous diagnosis of bipolar affective disorder, hypertension and obesity. According to the history, the patient was admitted to the psychiatric ward due to deterioration of her mental state for a month. She was found to have a high lithium level -2.98 mmol/L and elevated renal function parameters-creatinine 2.13 mg/dl. During treatment with hemodialysis, these parameters returned to normal. CONCLUSION: It is important to remember that lithium has a narrow therapeutic range. Attention should be paid during lithium treatment to situations that increase the risk of adverse effects and the development of toxicity, and serum lithium concentrations should be monitored during treatment.